Investor tastes: Implications for asset pricing in the public debt market - Shafron, Emily (Journal of Corporate Finance, 2019)
Some firms create innovative financial debt and equity products to attract specific investor tastes (i.e., non-monetary preferences unrelated to expected cash flows). Innovations can be costly, but they may also widen a firm's investor base, leading to a reduction in the cost of capital. Prior research is inconclusive about whether tailoring financial products to meet specific investor tastes affects asset pricing, which I posit stems from a lack of consensus on which assets satisfy a particular taste. My research design, however, avoids this ambiguity by testing the relation between asset pricing and an objectively identified investor taste—a taste for Shariah-compliant investments, which is satisfied via Islamic Finance. Using Malaysian data, I estimate price differences between conventional and Shariah-compliant bonds over an eight-year period (2005 to 2013). I find that an investor taste for Shariah-compliant bonds significantly affects bond pricing. These results hold even after controlling for issuer and issuance characteristics, including differences in covenant types, as well as the possibility that price and demand may be simultaneously determined. I also find evidence that investors with a taste for Shariah-compliant bonds have a significantly different demand distribution than investors without this taste, corroborating my assertion that a preference for Shariah-compliant investments is a distinct taste. Overall, my results are consistent with investors taste affecting the cost of capital.